The evaluation of the qualities of mind mapping module - Tee, Tze Kiong; Md. Yunos, Jailani; Othman, Widad; Yee, Mei Heong (2010)
Using Self-Instructional Modules within the technical education can be an alternative approach and make significant contributions. Modules are not just “job sheets’ or “old style work units” or “chapters of books” with questions added (Meyer, 1988). Module is a planned series of learning activities designed carefully to assist the learners to accomplish certain specific objectives (Abdul Razak, 2005; Muhamad Sam, 2005; Shaharom, 1994; Klingstedt, 1971). An attempt to develop and implement a modular approach on mind mapping techniques was made in the secondary school. This paper will discuss various components of this modular approach by referring to Meyer Model. Fleiss’s Kappa was used to determine the degree to which consensus agreement ratings vary from the rate expected by chance, with values greater than .60 indicating substantial non-chance agreement. Fleiss’s Kappa for the inter-rater reliability score was κ = .7167, S.E. = .0990, 95% C.I. = .5226 to .9107, which can be taken to represent constant agreement among raters. Eight raters (content and design experts) used the instrument to rate the qualities of the module. Analysis of the raters showed an agreement on satisfactory level and above on all 34 items.